Pengaruh Pemberian Jus Semangka Terhadap Penurunan Tekanan Darah Terhadap Penderita Hipertensi Pada Lansia Di Puskesmas Seputih Mataram Lampung Tengah Tahun 2019 - Sukawati, Ni Made Ari; Susilawati, Susilawati; Anggraini, Anggraini; Zarma, zarma (MIDWIFERY JOURNAL, 2023)
Hypertension or high blood pressure is a condition when the blood flows with higher pressure compared with the normal rate through the blood pressure. Based on the medical record at Seputih Mataram Health Center of Lampung Tengah Regency in 2017, hypertension placed the fifth position out of ten most common diseases happening on 1,513 male patients and 1,342 female patients; 2,856 people in total. On the following year, on January 2018, hypertension got the fourth position of ten most common diseases which happened on  52 male and 195 female patients; 247 patients in total. The management of hypertension can be done through pharmacologic and non-pharmacologic therapies. The non-pharmacologic therapy or complementary therapy can be done through consuming watermelon juice as the prevention and medication. The objective of this study was to identify the effect of watermelon juice consumption toward  blood pressure decrease on hypertensive elder patients at Seputih Mataram Health Center of Lampung Tengah Regency in 2019. This was a quantitative study with quasi experiment design. The population of this study consisted of the whole elder people with hypertension complaint registered at Seputih Mataram Health Center of Lampung Tengah Regency amounting to 52 people. The samples were 30 after doing purposive sampling technique. The data collection was observational sheets. The data analysis was through T-Dependent. The result of the study revealed that the frequency distribution average of the blood pressure before consuming watermelon juice was 148 mmHg with 7.88 Standard Deviation, the systole was 150 – 160 mmHg and the diastole was 90 – 100. The distribution frequency average of the blood pressure after consuming watermelon juice was 129 mmHg with 5.09 Standard Deviation, the systole was 120 – 150 and the diastole was 90 – 100. There was an effect of watermelon juice consumption toward blood pressure decrease on hypertensive elder people (p value 0.000 < 0.05). The elder people with hypertension problem should consume watermelon juice in order to control their blood pressure without using pharmacologic medication due to the side effect. Keywords: watermelon juice, hypertension, elder peopleABSTRAK Hypertension or high blood pressure is a condition when the blood flows with higher pressure compared with the normal rate through the blood pressure. Based on the medical record at Seputih Mataram Health Center of Lampung Tengah Regency in 2017, hypertension placed the fifth position out of ten most common diseases happening on 1,513 male patients and 1,342 female patients; 2,856 people in total. On the following year, on January 2018, hypertension got the fourth position of ten most common diseases which happened on  52 male and 195 female patients; 247 patients in total. The management of hypertension can be done through pharmacologic and non-pharmacologic therapies. The non-pharmacologic therapy or complementary therapy can be done through consuming watermelon juice as the prevention and medication. The objective of this study was to identify the effect of watermelon juice consumption toward  blood pressure decrease on hypertensive elder patients at Seputih Mataram Health Center of Lampung Tengah Regency in 2019. This was a quantitative study with quasi experiment design. The population of this study consisted of the whole elder people with hypertension complaint registered at Seputih Mataram Health Center of Lampung Tengah Regency amounting to 52 people. The samples were 30 after doing purposive sampling technique. The data collection was observational sheets. The data analysis was through T-Dependent. The result of the study revealed that the frequency distribution average of the blood pressure before consuming watermelon juice was 148 mmHg with 7.88 Standard Deviation, the systole was 150 – 160 mmHg and the diastole was 90 – 100. The distribution frequency average of the blood pressure after consuming watermelon juice was 129 mmHg with 5.09 Standard Deviation, the systole was 120 – 150 and the diastole was 90 – 100. There was an effect of watermelon juice consumption toward blood pressure decrease on hypertensive elder people (p value 0.000 < 0.05). The elder people with hypertension problem should consume watermelon juice in order to control their blood pressure without using pharmacologic medication due to the side effect. Keywords: watermelon juice, hypertension, elder people